Thanks for Your Recognition, Boss! a Study of How and When Voice Endorsement Promotes Job Performance and Voice - Wu, Shaoxue; Kee, Daisy Mui Hung; Li, Daiheng; Ni, Dan (Frontiers in Psychology, 2021)
Existing studies mainly explore the antecedents and distal outcomes of employees’ voice behavior. Little is known about what may occur after supervisors endorse employees’ ideas. Based on the conservation of resources theory, we explore how and when voice endorsement affects employees’ job performance and voice behavior. With the sample of 444 matched supervisor-subordinate pairs from a large organization, we find that supervisor’s voice endorsement positively influences employees’ voice behavior and job performance through the mediating effects of positive mood and work engagement. Additionally, we find that employees’ voice commitment strengthens the influence of supervisor’s voice endorsement on employees’ positive mood. Theoretical and practical implications of these findings are discussed.